Sonnet 101 with Prof. Pessoa: Fernando Pessoa’s Marginalia on an Anthology of 19th-Century English Sonnets - Pittella, Carlos (2017)
A 1902 edition of Sonnets from this Century was located in the estate of the late Portuguese architect Fernando Távora. The anthology displays inscriptions on 194 of its pages, starting with the signature “F. A. N. Pessôa.” This is not only a volume that once belonged to Fernando Pessoa, but a book no one even knew to exist, exhibiting a treasure of annotations. It offers insight into the deep relationship between the Portuguese poet and the English lyrical tradition. This dossier, preceded by an introduction, transcribes all the handwritten notes in the volume and presents facsimiled pages organized in thematic sections: general evaluations of sonnets according to Pessoa, Portuguese translations, notes on meter, rhyme and form, and other marginalia. This work aspires to serve as a model for editing annotations in any volume of Pessoa’s private library, as well as to open paths of inquiry, for every poem annotated in Sonnets of this Century may contribute to a better understanding of Pessoa’s works.